Comportamento de adesão da madeira de um híbrido clonal de Eucalyptus urophylla × Eucalyptus grandis proveniente de três condições de manejo - Plaster, Octávio Barbosa [UNESP]; Oliveira, José Tarcísio da Silva; Gonçalves, Fabrício Gomes; Motta, Javan Pereira (My University, 2012)
This study aimed to evaluate the adhesion ability of eucalyptus lumber from three tillage systems, using adhesives: resorcinol formaldehyde and two adhesives in water emulsion based on vinyl poly-acetate. The management systems were characterized by three strata, the stratum one (E1) characterized by wood from coppice and 70 months of age, the stratum two (E2) characterized by wood and retirement age of 166 months and stratum three (E3), also characterized by retirement at 70 months of age. The wood was derived from a random mixture of the first two sawn logs, each three feet from the base, which comprised three treatments on the adhesive used. We evaluated the shear strength by compression tests and the percentage of wood failure in the glue line. Based on the results obtained, it can be said that the adhesion had satisfactory performance with all the resins used, and the average values of shear strength of the glue line were shown to be equivalent to the shear strength of solid wood only for the samples which adhered with 'Wonderbond' adhesive and also provide higher values for wood failure (97.64%). The highest density present in the wood of the second stratum (E2) influenced only sticking with the resorcinol formaldehyde resin. For polyvinyl acetate (Cascorez 2590), shear values decreased in the third management condition (E3).
Behavior of wood adhesion in clonal hybrid Eucalyptus urophylla × Eucalyptus grandis originating from three management conditions
Keywords: Adhesive; Density; Sawn wood; Shear strength